Structures of Spoken Academic Clusters in Ted Talks - Panthong, Panupan; Rattanawaropas, Waridtha (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2021)
Academic clusters frame the thoughts between discourses. These clusters were extensively explored in a written discourse while few shed the light on spoken discourse. Therefore, this work aimed to explore the cluster list and analyze the structural patterns of spoken academic presentations in Ted Talk. The self-compiled corpus entitled ‘Pop Ted Talks’ included 183,275 running words retrieved from three poplar playlists in Ted Talk official website. Word Smith Tool version 7.0 was used to generate the spoken academic cluster lists. For the structural analysis, the clusters were classified into three main different types based on Biber et al. (2004)’s taxonomy. The results revealed that there were 62 cluster types with some of the socio-cultural clusters in the Pop Ted Talks corpus. Structurally, the noun phrase and prepositional phrase fragments covered almost half of the corpus (45.54%), followed by 40.32% of verb phrase fragments and 16.13 % of dependent clause fragments, respectively. This study found that clusters in Ted Talk shared similar characteristics with academic lecture genre.